Perley Gates Western: Bullets Don't Argue - Book 3 - Johnstone, William W.; Johnstone, J. A.; Kensington Publishing Corporation (New York, New York : Pinnacle Books/Kensington Publishing Corp., 2019)
"Once every year, Perley Gates and his brothers lead the Triple-G crew on its annual cattle drive. Its a treacherous journey along the Great Western Trail, with a herd of two-thousand cows on one side and many opportunities for trouble on the other. This year, trouble shows up in the form of a beautiful young woman, her little baby, and her bizarre traveling companion--a colorful old cuss who goes by the name of Possom Smith. Theyre heading to a settlement called Butcher Bottom, and risking their necks to get there. Perley--being the gentleman he is--offers to escort the trio to their destination. But there are a few minor details they forgot to tell Perley ... The woman is a widow whose husband had enemies. The old man is hiding a small fortune that might get them killed. And Perley is stuck in the middle trying to decide whos good, whos bad--and who deserves to die first."--
Keywords: Cowboys -- Fiction; Brothers -- Fiction; Cattle drives -- Fiction; Widows -- Fiction; Older men -- Fiction; Treasure troves -- Fiction; Voyages and travels -- Fiction; Frontier and pioneer life -- West (United States); Fiction; Buried treasure -- Fiction; Great Western Scenic Trail -- Fiction; West (United States -- Fiction; Western fiction